Assessment of the antifouling effect of five different treatment strategies on a seawater cooling system. (25th June 2015) - Rubio, Daniel; Casanueva, José F.; Nebot, Enrique
Abstract: Biofouling is a complex and important problem in cooling systems using water from natural sources such as lakes, rivers and sea. The first stage of biofilm formation is the colonization and uncontrolled microbial growth on surfaces. The aim of this study was to evaluate and to compare the effectiveness of different antifouling treatments in a heat exchanger cooled by seawater. Two types of experiments were carried out. Firstly, by employing a pilot plant simulating an industrial heat exchanger, chlorination and its combination with other treatments (UV and copper ions) were tested and the formed fouling was monitored and quantified. Then, the disinfection effectiveness of biocides employed was checked on two marine bacteria in order to identify the antifouling action mechanism. The combination of chlorine and copper was the most effective strategy for mitigation of fouling growth. After 60 days of testing, the thermal resistance showed no significant increase and the total solids accumulated inside the test tube were reduced by 70% compared to control treatment. The effectiveness of chlorine–copper treatment against fouling is probably due to a combination of their synergic inactivation mechanisms under prolonged exposure times, such as those of fouling experiments (60 days). The effectiveness of antifouling treatment was not only affected by the concentration of chlorine in the cooling water, but also by the dosage pattern. A chlorine peak of 0.4 mg L −1 for 1 h a day over the concentration of control (0.12 mg L −1 ) was able to reduce the increment in Rf and the accumulation of solids by approximately 50%. The combined use of chlorine and copper as antifouling treatment can be recommended in specific cooling systems that use seawater. Highlights: Five antifouling treatment strategies on a seawater cooling system were evaluated. All the tested treatments in the pilot plant improved the control treatment. The chlorine–copper combination was the most effective antifouling strategy. The biocides employed were tested in the disinfection of two marine bacteria. The parameter Rf resulted very useful for monitoring the fouling progression.